Long-term Results in Children with Henoch-Schönlein Nephritis - Caner ASLAN; Nilufer GOKNAR; Emre KELESOGLU; Diana UCKARDES; Cengiz CANDAN (Medeniyet Medical Journal)
Objective: Henoch-Schönlein purpura (HSP) is a small vessel vasculitis and palpable purpura, with arthritis, gastrointestinal as abdominal pain, and renal involvement as typical clinical findings. The most important prognostic factor for HSP vasculitis is renal involvement. This study aimed to investigate the relationship between clinical, laboratory, and histopathologic findings of children with HSP nephritis with long-term renal prognosis. Methods: This retrospective study included children with HSP nephritis between January 2010 and December 2019. Initial clinical presentation, laboratory findings, and kidney biopsy results were obtained, and treatment modalities were recorded and classified using the Meadow classification and grouped into mild and severe cases. Additionally, data at the last follow-up were analyzed and classified. Results: A total of 90 children (59 male) with a mean age of 8.8+-3.2 years were included. According to initial clinical findings, 18 children were in the Meadow's severe group. Fifteen (15/72) children in the mild group and all children in the severe group had undergone kidney biopsy. The severe group had higher histopathologic stages compared to the mild group (p=0.022). Immunosuppressive treatments were used in 44.4% of mild cases and 100% of severe cases (p<0.01). On follow-up, only four children (two in the mild group) had persistent proteinuria. Conclusions: Severe clinical findings in the initial presentation were related to more intensive immunosuppressive treatment. Additionally, renal histopathological stages were higher in the severe group. Long-term follow-up for proteinuria is mandatory for all children with HSP nephritis, even with mild initial clinical findings.